2018
DOI: 10.1210/jc.2018-00724
|View full text |Cite
|
Sign up to set email alerts
|

Does AMH Relate to Timing of Menopause? Results of an Individual Patient Data Meta-Analysis

Abstract: AMH was a significant predictor of TTM and especially of time to early menopause. However, individual predictions of age at menopause demonstrated a limited precision, particularly when concerning early age at menopause, making clinical application troublesome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 19 publications
1
55
1
3
Order By: Relevance
“…Every AMH level decrease of around 0.10 ng/mL was related with a 14% increased risk of early menopause (p < 0.001). Furthermore, a metaanalysis of 2,596 female patients (of whom 1,077 were menopausal) showed that the combination of AMH and age was more reliable in the prediction of early menopause than age alone [53]. Despite all the studies, more accurate threshold for AMH level needs to be defined, and other variables, such as family history of early menopause, maternal age at menopause, and lifestyle factors (smoking, body mass index [BMI], use of alcohol, and parity) should also be considered.…”
Section: Use As a Marker For Predicting Age At Menopausementioning
confidence: 99%
“…Every AMH level decrease of around 0.10 ng/mL was related with a 14% increased risk of early menopause (p < 0.001). Furthermore, a metaanalysis of 2,596 female patients (of whom 1,077 were menopausal) showed that the combination of AMH and age was more reliable in the prediction of early menopause than age alone [53]. Despite all the studies, more accurate threshold for AMH level needs to be defined, and other variables, such as family history of early menopause, maternal age at menopause, and lifestyle factors (smoking, body mass index [BMI], use of alcohol, and parity) should also be considered.…”
Section: Use As a Marker For Predicting Age At Menopausementioning
confidence: 99%
“…Menopause occurs when the number of remaining follicles falls below a critical threshold and the ovaries are no longer able to generate mature oocytes or maintain a menstrual cycle. 17 It appears that the end of natural fertility occurs at some point, approximately 10 years, before this point, though the ovaries maintain normal hormone secretion until 3-4 years before the menopausal transition. 3,17 Several studies have suggested that using AMH in addition to age can possibly predict timing of menopause in late reproductive-age women.…”
Section: Amhmentioning
confidence: 99%
“…17 It appears that the end of natural fertility occurs at some point, approximately 10 years, before this point, though the ovaries maintain normal hormone secretion until 3-4 years before the menopausal transition. 3,17 Several studies have suggested that using AMH in addition to age can possibly predict timing of menopause in late reproductive-age women. 2,17 However, other studies have suggested that these predictions may be too broad and less accurate at the extremes of age of menopause, limiting their clinical utility.…”
Section: Amhmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated surgery for OMA has a higher risk of complications compared with primary endometrioma (68), and accumulation of postoperative adhesions over a lifetime may affect future fertility. Moreover, low AMH levels following surgery are predictive of earlier menopause and a shorter reproductive lifespan (69,70).…”
Section: Impact Of Endometrioma and Its Excision On Spontaneous Concementioning
confidence: 99%